Noun inflectional system of interslavic language - Kupchenko Alona; Kupriianov Yevhen (онлайн, 2020)
Linguistics nowadays is extending the limits of theory. Many systems of morphological analysis, synthesis and lemmatization that focus on the grammatical specificity of the appropriate language have been developed in recent decades. Interlsavic language that has recently emerged is gaining popularity. Thus, we have formalized the model for the noun inflectional paradigm of Interslavic language This article describes the noun inflectional paradigm of Interslavic language developed on the basis of the Shirokov`s inflectional paradigm. Also, this study analyzes the grammar states of the noun in paradigm classes. The author suggests differentiation of grammatical groups and paradigmatic classes for Interslavic language.
Keywords: inflection, inflectional paradigm, inflectional system, quasiflexions, quasi-stem, Interslavic language